Assessment of Pressurised Metered Dose Inhaler Technique of Nursing Staff in Different Government Hospitals of Karachi - Sundeep Sahitia; Syed Imtiaz Ahmed Jafry; Syed Muhammad Zulfiqar Hyder Naqvi; Nargis Anjum; Adnan Anwar (KARACHI MEDICAL AND DENTAL COLLEGE, 2018)
Objective: To assess pressurised metered dose inhaler technique of the nursing staff in different government hospitals of Karachi. Methods: A cross-sectional study was carried out in four randomly chosen government hospitals  of Karachi. After checking for study criteria and obtaining written informed consent, a total of 120 nurses   were interviewed and then given a placebo inhaler to demonstrate their inhaler technique. The reference for assessment was the 12-step  inhalation  technique  suggested  by  the  American  College  of  Chest Physicians. Results: The study results revealed that out of  the  12  steps  of  the  inhaler  technique,  only  3  steps were followed by a majority of the study participants i.e. taking the cap off (64.2%), putting the metered dose inhaler in mouth with lips sealed (59.2%) and breathing in slowly  by  pressing  down  the metered dose inhaler (62.5%). The mean inhaler technique score of the study participants was 3.18 ± 2.34 out of 12 and only 1 (0.8%) of them had correct inhaler technique. Furthermore, the mean inhaler technique score was significantly higher for higher education level (p=0.001) and greater experience (p<0.001). Conclusion: The study results demonstrated the acute deficiency of knowledge  about  the  correct  in- haler technique among the study  nurses.  Appropriate  resources  should  be  directed  towards  educat-  ing nurses to make sure that their needed knowledge and skills stay updated.